Changed dynamic ventilation parameters as a result of a breathing exercise intervention program - Bahenský, Petr; Malátová, Renata; Bunc, Václav (The Journal of sports medicine and physical fitness, 2019)
BACKGROUND: The performance of the respiratory system during the exercise is limiting the final performance in endurance disciplines. The quality of breathing is linked to endurance performance, subject´s training state, intensity and duration of the physical load, the implementation of which, thus the economy of breathing, is possible to influence through a targeted breathing exercise. The aim of this study is to evaluate the effect of breathing intervention exercises on the effectiveness of breathing by monitoring value of tidal volume (VT) and breathing frequency (BF) during an endurance type load in adolescent endurance runners. METHODS: Thirty-seven 37 adolescent endurance runners were enrolled in this study. The girls were 16.79±1.51 years old, the boys were 16.5±1.8 years old. They are involved in endurance training for at least one year. Twenty-one probands took part in the intervention scheme; sixteen probands formed the control group. The study investigated the effect of two months and four months of breathing exercise intervention on tidal volume VT and BF. RESULTS: The probands carried out breathing exercises, which took an average of 13.1±3.7 minutes per day over the first two months, and an average of 11.1±3.9 minutes per day over the next two months. The breathing economy was significantly changed as a result of respiratory exercise intervention. Already after 2 months of intervention there was a significant decrease of BF (by 5.92%) and a significant increase of VT (by 4.44%). After another 2 months, the changes were even more pronounced. In the 4 months of the intervention, the BF decreased by 11.47% and the VT increased by 10.96% in comparison to the original state. In the control group, there were no significant changes. CONCLUSIONS: It was confirmed that the two-month breathing exercise intervention focused on the activation of the diaphragm is sufficient and resulted in significant changes of in VT and BF.
Keywords: fyzická vytrvalost; Male; Breathing Exercises; dechová cvičení; plíce; Adolescent; mužské pohlaví; Exercise; mladiství; Respiration; Lung; běh; lidé; Physical Endurance; ženské pohlaví; Humans; Running; Female; cvičení; dýchání